Au-Catalyzed Synthesis and Functionalization of Heterocycles - Bandini, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Synthesis of Oxygenated Heterocyclic Compounds via Gold-Catalyzed Functionalization of π-Systems--Jose L. Mascareñas , Fernando López Gold-Catalyzed Synthesis of Nitrogen Heterocyclic Compounds via Hydroamination Reactions--Antonio Arcadi Synthesis of Oxygenated and Nitrogen Containing Heterocycles by Gold-Catalyzed Alkyne Oxidation--Longwu Ye and Liming Zhang Synthesis of Heterocyclic Compounds via Gold-Catalysed Enyne Rearrangements--María Teresa Quirós and María Paz Munoz C-H Functionalisation of Heteroaromatic Compounds via Gold Catalysis--Nanna Ahlsten, Xacobe C. Cambeiro, Gregory J.P. Perry,and Igor Larrosa Enantioselective Gold-Catalyzed Synthesis of Heterocyclic Compounds--Dillon H. Miles and F. Dean Toste Gold Catalysis in the Synthesis of Natural Products: Heterocycle Construction via Direct C-X-Bond-Forming Reactions--Yu-Hui Wang, Zhong-Yan Cao, Jian Zhou.
Synthesis of oxygenated heterocyclic compounds via gold catalyzed functionalization of π-systems -- Gold catalyzed synthesis of nitrogen heterocyclic compounds by hydroamination reactions -- Synthesis of oxygenated and nitrogen-contained heterocycles bygold-catalyzed alkyne oxidation -- Synthesis of Heterocyclic compounds via gold-catalyzed enyne rearrangements -- C-H functionalization of heteroaromatics via gold catalysis -- Enantioselective gold catalyzed synthesis of heterocyclic compounds -- Gold catalysis in the synthesis of heterocyclic natural products.
Keywords: Organometallic chemistry .; Chemistry, Organic; Catalysis; Organometallic Chemistry; Organic Chemistry; Catalysis